2010
DOI: 10.1111/j.1600-079x.2010.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Update on the use of melatonin in pediatrics

Abstract: :  Melatonin, an endogenously produced indoleamine, is a highly effective antioxidant, free radical scavenger, and a primary circadian regulator. Melatonin has important antioxidant properties owing to direct and indirect effects. It directly scavenges reactive oxygen and reactive nitrogen species, prevents molecular oxidation, improves mitochondrial physiology, and restores glutathione homeostasis. Its indirect antioxidant effects stem from its ability to stimulate the activities of the enzymes involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 148 publications
(207 reference statements)
2
51
0
3
Order By: Relevance
“…The analgesic, anti-inflammatory, anti-anxiety, and anti-agitation effects of melatonin have been shown in several studies (10). Several studies have reported that melatonin, given as preoperative premedication, is associated with sedation and preoperative anxiolysis without mental dysfunction including the memory recall and driving performances or the quality of recovery.…”
Section: Introductionmentioning
confidence: 95%
“…The analgesic, anti-inflammatory, anti-anxiety, and anti-agitation effects of melatonin have been shown in several studies (10). Several studies have reported that melatonin, given as preoperative premedication, is associated with sedation and preoperative anxiolysis without mental dysfunction including the memory recall and driving performances or the quality of recovery.…”
Section: Introductionmentioning
confidence: 95%
“…It is a highly effective antioxidant, scavenging hydroxyl radicals and inhibiting the production of nitric oxide (Gitto et al, 2011;Serel et al, 2004) and other antioxidants like vitamins E and C (Kücükakin et al, 2009). The ability of melatonin to counteract ROS formation is due to the special characteristic of this substance to cross morpho and physiological barriers distributed in tissues, cells and sub-cellular compartments due to its distinct physical and chemical properties (Costa et al, 1995;Tomás-Zapico et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Dosis de 1-5 mg producen en 1 h concentraciones plasmáticas que son 10-100 veces mayores que las del pico máximo nocturno, para descender a los valores normales en 4-8 h 35,36 .…”
Section: Dosificaciónunclassified
“…Basándonos en las series de casos y ensayos clínicos publicados (todos en mayores de un año), debe administrarse a la misma hora y entre 30-60 min antes de la hora habitual de ir a dormir 35 .…”
Section: Momento De Administraciónunclassified